The Thirty-Ninth Yearbook of the National Society for the Study of Education: Intelligence: Its Nature and Nurture, Part II, Or
DOI: 10.1037/11228-006
|View full text |Cite
|
Sign up to set email alerts
|

A second study of familial resemblance in intelligence: Environmental and genetic implications of parent-child and sibling correlations in the total sample.

Abstract: This chapter describes a continuation of a previous study (12) that appeared in the Twenty-Seventh Yearbook of this Society. The earlier report was based on intelligence measurements of husband, wife, and two or more children in each of 105 families. The present study is based on 997 cases in 269 family groups, including the previous 105 families, and 164 additional families of two or mare members.Studies of familial resemblance impose no direct control on either heredity or environment, and for this reason ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 6 publications
0
14
1
Order By: Relevance
“…There does not seem to be any trend towards correlations with the mothers' scores being any higher or lower than the fathers' scores for either sons or daughters. This seems to refute any conjecture about the environmental power of the early rearing of the mother over that of the father (Conrad & Jones, 1940). …”
Section: Correlational Analysismentioning
confidence: 60%
See 3 more Smart Citations
“…There does not seem to be any trend towards correlations with the mothers' scores being any higher or lower than the fathers' scores for either sons or daughters. This seems to refute any conjecture about the environmental power of the early rearing of the mother over that of the father (Conrad & Jones, 1940). …”
Section: Correlational Analysismentioning
confidence: 60%
“…This correlational method is unsatisfactory for providing evidence of genetic influences, especially in behavioral traits, since it is nearly impossible to separate the effects of environment from those of heredity. Contrary to this opinion, Conrad and Jones (1940) maintained that if mother-son and mother-daughter correlations are approximately equal to father-son and father-daughter correlations, it is evidence for a genetic influence on the trait. They reason that if environmental effects predominate, the mother-child coefficients should be higher than those of father-child because of her greater influence during the formative years.…”
Section: Correlational Analysismentioning
confidence: 86%
See 2 more Smart Citations
“…Other investigators have demonstrated that monozygotic twins are more similar in IQ than dizygotes, and that the correlation between the IQ of parent and child is moderately high (r = .50 to .60) (3,4,9). These data:…”
Section: A Introductionmentioning
confidence: 94%